Deciding right – the UKs first regional integration of advance care decisions. Issue Volume 2:Issue (2012)Supplement 1 (1st March 2012) - Regnard, Claud
Abstract : The need for clear decisions and protocols during emergencies has to be balanced against the need to make decisions that avoid unnecessary or distressing treatment. A regional initiative has the potential to centre decisions on the individual rather than the organisation. The challenge is to ensure that individuals and carers make informed choices, and that the decisions are communicated efficiently and effectively. The North East SHA Deciding Right initiative provides the principles by which all health organisations can set their policies to encourage this partnership around care decisions made in advance for people who may lose capacity in the future. These principles Centre care decisions on the individual rather than the organisation Strongly endorse the partnership between the patient, carer or parent and the clinician Are based on the 2005 Mental Capacity Act and the latest national guidelines on advance care planning Recognise the individual with capacity as key to making care decisions in advance Identify the triggers for making care decisions in advance Create regional documentation for use in any setting that is recognisable by all health and social care professionals. Regional documents have been established for Advance Decisions to Refuse Treatment (ADRT), Do Not Attempt Cardiopulmonary Resuscitation (DNACPR) and Emergency Health Care Plans (EHCPs) Recognise the Liverpool Care Pathway for the Dying document as a DNACPR order Minimise the likelihood of unnecessary or unwanted treatment Introduce Emergency Health Care Plans as an important adjunct in specialist care settings to tailor care to the individual with complex needs Create principles and documentation suitable for all ages (children, young people and adults) This is the first regional initiative in the UK to integrate the principles of making care decisions in advance for children, young people and adults.